Review: Dual Band Microstrip Antennas for Wireless Applications - Rakesh Kumar Bajpai; Rajeev Paulus; Ashish Singh; Mohammad Aneesh (International Journal of Advances in Applied Sciences, 2018)
In this manuscript, a review of dual band microstrip antennas for wireless communication is presented. This review manuscript discusses regarding the geometric structures, different methods of analysis for antenna characteristics, and different types of wireless applications.